Human Rights as Human Independence A Philosophical and Legal Interpretation - Montero, Julio (Pennsylvania Studies in Human Rights, 2022)
Can human rights be claimed against agents other than states, such as transnational corporations and global governance institutions? Does the authority of human rights depend on international law-making, or do they have a moral status that must be honored even in the absence of legal structures? What obligations do human rights impose on states acting across borders? What does it mean that the international community must work together to bring about their universal realization? Do we have human rights to abortion, same-sex marriage, and fully democratic government? What must individuals do for the human rights of others?Although these questions may be essential for the future of global politics and international relations, human rights doctrine offers no conclusive answers for them. In Human Rights as Human Independence, Julio Montero develops an original theory of human rights that helps us think about these and similar issues. Montero argues that human rights regulate the conduct of sovereign political agents both within and beyond borders, and that the aim of human rights norms is to protect everyone's fundamental moral claim to enjoy an equal sphere of agency to develop their personality.Human Rights as Human Independence offers a comprehensive, systematic, and complete account of the nature, sources, and scope of human rights that can be used to interpret international documents and make informed decisions about how human rights practice must be continued in the years to come. The book is thus of interest for a wide audience, ranging from philosophers and political theorists to lawyers, human rights scholars, and activists